UNDERSTANDING OF INCOME TAX BY INDIVIDUAL TAXPAYERS EMPLOYEES - SHERLIE EVABIONI LATUAMURY; RASNI HANIPA USEMAHU (CV KULTURA DIGITAL MEDIA, 2023)
Tax is a very significant source of state revenue. Various tax subjects and objects are determined by the government to take funds from the community. Individual tax is one type of tax applied. The purpose of this study is to determine the perception of individual income tax, on workers in one business / company. This research method is descriptive quantitative with interview techniques, documentation and obeservation in the field. The results showed that the understanding of income tax on individual taxpayers employees and about tax sanctions but do not understand what penalties are received if they do not pay taxes. is still very minimal.